A Study on High-Risk Pregnancy and Its Management: Role of Obstetric Nurses in Improving Maternal and Fetal Outcomes - Vazahid Khan; Ananda Nimmy; Sarika Samson (International Journal of Midwifery Nursing And Practices, 2026)
High-risk pregnancy is a major challenge in maternal and neonatal healthcare and is associated with increased morbidity and mortality among mothers and new-borns, particularly in developing regions where access to quality healthcare services remains uneven, this article examines the concept, classification, risk factors, pathophysiology, and management of high-risk pregnancy with a strong focus on the role of obstetric nurses in improving maternal and fetal outcomes, obstetric nurses play a central role in early identification of complications, continuous monitoring, implementation of evidence-based interventions, and patient education across antenatal, intrapartum, and postnatal periods, nurse-led care has been shown to reduce complications such as preeclampsia, gestational diabetes, preterm birth, and postpartum hemorrhage while improving patient satisfaction and adherence to treatment, despite advancements in maternal healthcare, challenges such as inadequate training, high workload, and limited resources continue to affect nursing effectiveness, therefore strengthening nursing education, promoting skill-based training, and ensuring institutional support are essential for optimizing outcomes, this article highlights the importance of empowering obstetric nurses and integrating their role into maternal healthcare systems to achieve better clinical outcomes and reduce maternal and neonatal mortality.
Keywords: High-risk pregnancy. obstetric nursing. maternal outcomes. fetal outcomes. antenatal care. nursing management. pregnancy complications. maternal health